2015
DOI: 10.1210/en.2015-1575
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin Is Required for GnRH Signaling to L-Type Calcium Channels and Activation of ERK

Abstract: We have shown that GnRH-mediated engagement of the cytoskeleton induces cell movement and is necessary for ERK activation. It also has previously been established that a dominant negative form of the mechano-GTPase dynamin (K44A) attenuates GnRH activation of ERK. At present, it is not clear at what level these cellular events might be linked. To explore this, we used live cell imaging in the gonadotrope-derived αT3-1 cell line to determine that dynamin-green fluorescent protein accumulated in GnRH-induced lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Cells were fixed in 4% PFA and then stained with Alexa 488-conjugated phalloidin and DAPI and imaged by CLSM. Our results confirm our previous studies that actin remodeling occurs following GnRHa stimulation (Edwards et al, 2016; Navratil et al, 2014; Navratil et al, 2007). Consistent with mTORC1 not effecting ERK activity, pretreatment with RAPA did not affect actin reorganization.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Cells were fixed in 4% PFA and then stained with Alexa 488-conjugated phalloidin and DAPI and imaged by CLSM. Our results confirm our previous studies that actin remodeling occurs following GnRHa stimulation (Edwards et al, 2016; Navratil et al, 2014; Navratil et al, 2007). Consistent with mTORC1 not effecting ERK activity, pretreatment with RAPA did not affect actin reorganization.…”
Section: Resultssupporting
confidence: 93%
“…Thus, understanding the mechanisms that GnRH utilizes to engage actin has important implications for fertility regulation. Previously, our group found that dynamin and cortactin are two key cell signaling intermediates that associate to engage the actin cytoskeleton following GnRH activation (Edwards, Dang, Murtazina et al, 2016; Navratil et al, 2014). Beyond this work, the full cohort of signaling mechanisms that GnRH utilizes to engage actin remodeling remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this data, αT3-1 cells transfected with K44A resulted in a loss of GnRH-induced actin remodeling events ( 62 ). Our group also demonstrated that pharmacological inhibition of dynamin GTPase activity, using both dynasore and dyngo, not only perturbed GnRH-induced actin reorganization but also significantly suppressed ERK activation ( 63 ). Thus, highlighting the importance of dynamin GTPase activity in actin reorganization and subsequent MAPK activation.…”
Section: Gonadotrope Signaling To Actinmentioning
confidence: 88%
“…28,29 Recent studies by Edwards and colleagues extended our understanding of the mechanisms of the role of actin cytoskeleton in GnRH signaling via L-type Ca 2þ channels and ERK activation. 30 Dynamin is a membrane-associated GTPase that is involved in membrane constriction, vesiculation, and cell wall formation. 31 Disrupting dynamin signaling in gonadotropes has long been known to disrupt GnRH signaling to the ERK pathway [32][33][34] ; however, the mechanistic basis for this has not been fully appreciated.…”
Section: Gnrh Action and The Actin Cytoskeletonmentioning
confidence: 99%
“…Actin cytoskeletal remodeling, necessary for gonadotropin secretion, is dependent on cortactin localization and these studies implicate dynamin signaling and calcium influx through Ltype Ca 2þ channels in this process. 30…”
Section: Gnrh Action and The Actin Cytoskeletonmentioning
confidence: 99%